Single influenza A viruses induce nanoscale cellular reprogramming at the virus-cell interface - Lukas Broich; Hannah Wullenkord; Maria Kaukab Osman; Yang Fu; Mathias Müsken; Peter Reuther; Mark Brönstrup; Christian Sieben (Nature Communications)
Abstract During infection, individual virions trigger specific cellular signaling at the virus-cell interface, a nanoscale region of the plasma membrane in direct contact with the virus. However, virus-induced receptor recruitment and cellular activation are transient processes that occur within minutes at the nanoscale. Hence, the temporal and spatial kinetics of such early events often remain poorly understood due to technical limitations. To address this challenge, we develop a protocol to covalently immobilize labelled influenza A viruses on glass surfaces before exposing them to live epithelial cells. Our method extends the observation time for virus-plasma membrane association while minimizing viral modifications, facilitating live imaging of virus-cell interactions. Using single-molecule super-resolution microscopy, we investigate virus-receptor interaction showing that viral receptors exhibit reduced mobility at the virus-binding site, which leads to a specific local receptor accumulation and turnover. We further follow the dynamics of clathrin-mediated endocytosis at the single-virus level and demonstrate the recruitment of adaptor protein 2 (AP-2), previously thought to be uninvolved in influenza A virus infection. Finally, we examine the nanoscale organization of the actin cytoskeleton at the virus-binding site, showing a local and dynamic response of the cellular actin cortex to the infecting virus.